A challenging strategy toward severe maternal outcome adversed from systemic lupus erythematosus and nephrotic syndrome in pregnancy: a case report - Manuaba, Ida Bagus Gde Fajar Manuaba; Mahayasa, Putu Doster Mahayasa; Nyoman Gede Budiana; Kamajaya, I Gusti Ngurah Agung Trisnu Kamajaya; Andrian, Samuel Albert Andrian (Indonesian Journal of Perinatology, 2024)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disorder that affects multiple organ systems, characterized by the production of autoantibodies and a wide range of symptoms resulting from damage to vital organs. Renal involvement is observed in approximately 40% of SLE patients and can present as various forms of glomerulonephritis, including membranous lupus nephritis, diffuse proliferative glomerulonephritis, and minimal-change nephropathy (MCN), particularly in cases associated with nephrotic syndrome. This case report highlights the therapeutic challenges in managing women with severe SLE and nephrotic syndrome during pregnancy and the postpartum period. Case presentation: A 21-year-old woman at 37 weeks of gestation presented with a history of nephrotic syndrome secondary to severe SLE. She was diagnosed with nephrotic syndrome at 30 weeks of pregnancy, with differential considerations including pregnancy complications and severe SLE activity (ACR/EULAR score 10). Additional diagnoses included lupus nephritis, stage II hypertension, mild anemia (hemoglobin 8.9 g/dL), hypoalbuminemia (1.5 g/dL), hypercholesterolemia, anasarca edema, oligohydramnios, and a non-reactive non-stress test (NST). An emergency cesarean section was performed successfully, after which the patient was admitted to the high-care unit for close postoperative monitoring. Post-surgery, she received multidisciplinary management involving an intensivist and a nephrologist. Conclusion: This study explores the interplay between SLE and nephrotic syndrome, focusing on their impact on maternal and fetal health during pregnancy. It highlights the importance of a multidisciplinary approach in managing these conditions to mitigate the risk of severe maternal and fetal complications.